The particle SSV1 from the extremely thermophilic archaeon Sulfolobus is a virus: demonstration of infectivity and of transfection with viral DNA. - Schleper, C (1992)
The lemon-shaped "virus-like" particle SSV1 produced by the thermophilic archaeon Sulfolobus shibatae has not previously been observed to infect any host. Using a plaque assay suitable for the extreme growth conditions of this archaeon, we have shown infection of Sulfolobus solfataricus by SSV1. Upon infection, the viral genome was always found integrated into a tRNA gene of the host chromosome, a situation similar to that in S. shibatae, proving that site-specific integration is involved in establishing the lysogenic state. As in S. shibatae, UV-irradiation of lysogenized S. solfataricus led to virus production apparently not accompanied by cell lysis. We have also demonstrated the efficient uptake of exogenous DNA and its expression in Sulfolobus by transfecting S. solfataricus with SSV1 DNA by electroporation. Transfection efficiencies of up to 10(6) transfectants per microgram of DNA were obtained.